Determinant Factors On Firm Value Of Manufacturing Industry - Putri Indah Wibowo; Achmad Saiful Ulum (MediaTrend, 2022)
Destinationfrom this research is to examine Determinant Factors On Firm Value Of Manufacturing Industry. This study uses a quantitative approach. The data collection technique used in this research is the documentation method, namely by collecting data from complete financial reports that have been published by the company through the official website of the Indonesia Stock Exchange (IDX), namelywww.idx.co.id. The sampling technique used was purposive sampling method with a sample of 50 companies. The data analysis method used is multiple linear regression analysis using SPSS version 16 software application. The results show that simultaneously profitability, leverage, investment decisions, liquidity and managerial ownership have a significant effect on firm value. Partially profitability, investment decisions, liquidity, managerial ownership have no effect on firm value and leverage has a significant positive effect on firm value.Keywords: profitability, leverage, investment decisions, liquidity and managerial ownership, firm value